Meningkatkan Hasil Belajar Siswa Melalui Pembelajaran Kooperatif Pada Pembelajaran Tari Di Kelas VIII 5 SMPN 25 Padang - Yuni Oktaviani; Yuliasma Yuliasma; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2019)
This article aimed to describe an improvement in students’ learning outcomes through cooperative learning in dance learning in class VIII 5 of SMP 25 Padang. The type of this research was Classroom Action Research. The procedure of this study consisted of 2 cycles, namely cycle I and cycle II. The research instrument was a knowledge test and a skill test. The techniques of data data collection were carried out by means of knowledge tests, skills tests and observations. Student completeness data were analyzed using individual and group completeness criteria with minimum completeness criteria of 70%. The results showed that through cooperative learning, students’ learning outcomes could be. It could be seen in the average value from cycle 1 to cycle 2. On the first cycle, there was an average value of 64.5 students with the number of completeness of 14 students (43.75%) from 32 students, and those who did not complete 18 students (56.25%) or under KKM (70). For the second cycle, the learning outcomes of the students' average score were 79 with the percentage of students who scored above 70 increased to 27 students (84.38%), and students who scored below 70 decreased to 5 students (15.62%). Thus, cooperative learning improves dance learning outcomes in class VIII.5 of SMPN 25 Padang.